AB0012 ROLE OF IRF5 GENE ON THE PATHOGENESIS OF IMMUNOGLOBULIN-A VASCULITIS. (2nd June 2020) - Remuzgo Martinez, S.; Genre, F.; Pulito-Cueto, V.; Prieto-Peña, D.; Atienza-Mateo, B.; Sevilla, B.; Llorca, J.; Ortego, N.; Lera-Gómez, L.; Leonardo, M.; Peñalba, A.; Cabero, M. J.; et al.
Abstract : Background: Interferon signaling pathway plays a relevant role in autoimmunity. Genetic variants in the interferon regulatory factor (IRF) 5 gene, that encodes the major regulator of the type I interferon induction [1], have been related to the development of several inflammatory diseases [2]. Objectives: To determine the influence of IRF5 on Immunoglobulin-A vasculitis (IgAV), an inflammatory vascular disease. Methods: Three IRF5 polymorphisms (rs2004640, rs2070197 and rs10954213) representative of 3 different haplotype blocks were genotyped in 372 Caucasian patients with IgAV and 876 sex and ethnically matched healthy controls. Results: No statistically significant differences between patients with IgAV and controls were observed when each IRF5 polymorphism was analyzed independently. Similarly, no statistically significant differences between patients with IgAV and controls were found when IRF5 polymorphisms were evaluated combined conforming haplotypes. Additionally, there were no statistically significant differences in genotype, allele and haplotype frequencies of IRF5 when patients with IgAV were stratified according to the age at disease onset or to the presence/absence of gastrointestinal or renal manifestations. Conclusion: Our results do not support an influence of IRF5 on the pathogenesis of IgAV. References: [1]Nat Immunol 2011; 12: 231-8; [2]Arthritis Res Ther 2014; 16: R146. Acknowledgments: This study was supported by European Union FEDER funds and "Fondo de Investigaciones Sanitarias" (grant PI18/00042) from 'Instituto de Salud Carlos III' (ISCIII, Health Ministry, Spain). RL-M is a recipient of a Miguel Servet type I programme fellowship from the ISCIII, co-funded by the European Social Fund (ESF, `Investing in your future´) (grant CP16/00033). SR-M is supported by funds of the RETICS Program (RD16/0012/0009) (ISCIII, co-funded by the European Regional Development Fund (ERDF)). VP-C is supported by a pre-doctoral grant from IDIVAL (PREVAL 18/01). LL-G is supported by funds of PI18/00042 (ISCIII, co-funded by ERDF). Disclosure of Interests: Sara Remuzgo Martinez: None declared, Fernanda Genre: None declared, Verónica Pulito-Cueto: None declared, D. Prieto-Peña: None declared, Belén Atienza-Mateo: None declared, Belén Sevilla: None declared, Javier Llorca: None declared, Norberto Ortego: None declared, Leticia Lera-Gómez: None declared, Maite Leonardo: None declared, Ana Peñalba: None declared, María Jesús Cabero: None declared, Luis Martín-Penagos: None declared, Jose Alberto Miranda-Filloy: None declared, Antonio Navas Parejo: None declared, Javier Sanchez Perez: None declared, Maximiliano Aragües: None declared, Esteban Rubio: None declared, MANUEL LEON LUQUE: None declared, Juan María Blanco-Madrigal: None declared, E. Galindez: None declared, Javier Martin Ibanez: None declared, Santos Castañeda: None declared, Ricardo Blanco Grant/research support from: Abbvie, MSD and Roche, Consultant of: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen and MSD, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Lilly and MSD, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Raquel López-Mejías: None declared